A rate-based TCP traffic model to accelerate network simulation. (April 2013) - Li, Ting; Van Vorst, Nathanael; Liu, Jason
Traditional discrete-event simulation of large-scale networks at the packet level is computationally expensive. This article presents a fast rate-based transmission control protocol (RTCP) traffic model designed to reduce the time and space complexity for simulating network traffic whilst maintaining good accuracy. A distinct feature of the proposed model is that the transmission control protocol (TCP) congestion control behavior is represented using analytical models that describe the send rate at the traffic source as a function of the round-trip time and the packet loss rate at different phases of a TCP connection. Rather than modeling at the granularity of individual packets visiting the intermediate routers, the model approximates traffic flows as a series of rate windows, each consisting of a number of packets considered to possess the same arrival rate. The model calculates the queuing delays and the packet losses as these rate windows traverse the individual network queues along the flow path. The proposed RTCP model is able to achieve a performance advantage over other TCP models, by integrating analytical solutions and aggregating traffic using rate windows. Empirical results show that the RTCP model can correctly capture the overall TCP behavior and achieve a speedup of more than two orders of magnitude over the corresponding detailed packet-oriented simulation.